Ribosome Proteins Represented by RPL27A Mark the Development and Metastasis of Triple-Negative Breast Cancer in Mouse and Human - Zhao, Weipeng; Li, Xichuan; Nian, Weiqi; Wang, Jun; Wang, Xiaorui; Sun, Linlin; Zhu, Ye; Tong, Zhongsheng (Frontiers in Cell and Developmental Biology, 2021)
Triple-negative breast cancer (TNBC) is known to have a poor prognosis and limited treatment options. The lack of targeted therapies and poor prognosis of patients with TNBC have made it urgent to discover novel critical diagnosis and therapeutic targets in TNBC field. Here in the current study, we integrated the single cell RNA-sequencing (scRNA-seq) data from four normal mouse mammary tissues and four mouse breast tumors. Comparative analysis was conducted to identify the gene profiles of normal epithelial cells and cancer cells at different models. Surprisingly, two ribosomal protein genes, Rpl27a and Rpl15, were significantly upregulated in the cancer cells in all the TNBC models. Next, we accessed the scRNA-seq data from human primary and metastasis TNBC tissues and comparative analysis revealed gene profiles of human primary and metastasis TNBC cancer cells. Ribosomal protein genes, represented by RPL27A and RPL15, showed significantly upregulated expression in metastatic TNBC cancer cells. Pathway analysis on the upregulated genes of the metastatic TNBC cancer cells identified the key regulators and signaling pathways that were driving the metastasis of the TNBC cancer cells. Specifically, EIF2 signaling was significantly activated and major member genes of this signaling pathway were upregulated. In vitro study revealed that targeting RPL27A or EIF2 signaling in TNBC cell line, MDA-MB-231, significantly reduced cell migration and invasion. Altogether, these data suggested that RPL27A gene is conducting critical functions in TNBC cancer development and metastasis and is a potential therapeutic target for TNBC.